Endomyocardial fibrosis in a non‐tropical patient who presented with chest pain mimicking ACS and left ventricular thrombus, case report - Ahmad S. Matarneh (14777578) (2023)
Endomyocardial fibrosis in a non‐tropical patient who presented with chest pain mimicking ACS and left ventricular thrombus, case report Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.5021